Social Participation in Community Empowerment through the Development of Alamendah Tourism Village - Putri, Camelina; Atthahara, Haura; Resmana Adiarsa, Sopyan (Journal of Government Insight, 2025)
This study aims to analyze the experiences, perceptions, and meanings of community participation in the empowerment of the Alamendah Tourism Village. The research employs a qualitative approach with a phenomenological research design. The relevance of this study to the field of Government Science can be seen from several aspects. First, in designing and implementing the development of a tourism village, knowledge in government science helps local governments and related institutions formulate policies that support community empowerment and effective tourism program management. Second, government science emphasizes the importance of citizen participation in decision-making processes. The data analysis technique used in this study follows Creswell's Phenomenological Analysis, which includes the stages of data management, reading and memoing, describing, classifying, interpreting, and representing or visualizing. Data were collected through observation, interviews, documentation, and audiovisual materials. The results of the study indicate that social participation in community empowerment through the development of Alamendah Tourism Village proceeds through interrelated and complementary stages. The awareness stage successfully fosters community understanding of the importance of their role. The capacity-building stage enhances the skills and knowledge required for managing the tourism village. Finally, the empowerment stage grants autonomy and responsibility to the community, strengthening their independence and active participation.